Influence of oxygen partial pressure on the oxygen diffusion and surface exchange coefficients in mixed conductors. Issue 1 (January 2019) - Geffroy, P.-M.; Guironnet, L.; Bouwmeester, H.J.M.; Chartier, T.; Grenier, J.-C.; Bassat, J.-M.
Abstract: The performances of mixed ionic and electronic conductors is used in many applications, such as oxygen transport membranes or electrodes in solid oxide fuel cells. The performances of these systems depend mainly on two fundamental parameters including oxygen diffusion (DO ) and the oxygen exchange coefficient (k). This work focuses on the impact of the oxygen partial pressure on oxygen diffusion and surface exchange coefficients of mixed conducting materials, as reported studies are scarce in the literature. In this way, two different mixed conducting materials are studied, namely, La0.6 Sr0.4 Fe0.6 Ga0.4 O3-δ, a perovskite-type material, and the nickelate La2 NiO4+δ . The DO and k coefficients are determined by a specific oxygen permeation measurement and by the isotopic exchange depth profile method.